Effectiveness of a Flex Orthotic Splint on Hand Range of Motion for Older Adults: A Pilot Study. (1st June 2013) - Beaty, Jeff A.; Murphy, April L.
ABSTRACT: Objective: The purpose of this study was to examine the effectiveness of a flex orthotic splint (FOS) on hand range of motion (ROM) for residents in a nursing home experiencing a hand contracture as a result of stroke, joint contracture, or rheumatoid arthritis. Methods: Eight residents of a nursing facility, who were diagnosed as developing a hand contracture, agreed to participate in the study. Their selection was performed according to an ABAA design. Extension and flexion as well as abduction and adduction measurements were taken over an 8-week period (baseline, 4-week period, and 8-week period). Results: Repeated measures analysis of variance (ANOVA) revealed, of those finger and thumb joints demonstrating a statistically significant change, 77.8% ( n = 14) of the joints improved with respect to ROM. Conclusions: While the results indicate that an FOS improves hand ROM for residents experiencing a hand contracture, a larger sample size and randomization are recommended to confirm the findings of this pilot study.